P2-S2.02 Role of decision makers in the lives of migrant sex workers-focus on families: an qualitative assessment. (10th July 2011) - Ramanaik, S; Sabnis, V; Gurav, K; Banandur, P; Buzdugan, R; Halli, S; Blanchard, J
Abstract : Background: This study is aimed to understand the role of family members in decision-making process of female sex worker (FSW) migration and its impact on HIV risk, vulnerability and transmission dynamics in Bagalkot, Bijapur and Belgaum districts of Northern Karnataka and southern Maharashtra. Methods: Qualitative in-depth interviews were conducted with family members of the migrant and non-migrant female sex workers (FSWs) as a part of a large cohort study to understand the patterns and determinants of FSW migration from northern Karnataka to southern Maharashtra, South India. The present paper specifically focuses on the findings generated from in-depth, qualitative interviews with 30 family members of migrant and non-migrant (15 each) FSWs who entered into sex work through the traditional" devadasi system. Results: Economic factor is inherent in the sex work initiation and FSW migration. Families (mainly mother in the family) are playing a prominent role in the decision regarding the initiation, migration, selection of destinations, brothel madams, financial dealings and the contract agreement with brothel madams. Peer influence, economic status of a family and established contacts with destinations are supportive factors for FSW migration. Migrant sex workers are made to believe that they have the responsibility of fulfilling families' economic needs including the repayment of loans. Conclusions: Information on role of a decision maker in the lives of migrant sex workers can be used to decide regarding resource allocation and programmatic prioritisation. Building strong rapport with families and linking the place of origin and destination may increase the ability to reach FSWs at an early stage of sex work profession.